IDDF2018-ABS-0240 Role of human microbiota in skin dermatitis and eczema: a systematic review. (June 2018) - Lee, Learn-Han; Letchumanan, Vengadesh; Khan, Tahir Mehmood; Long, Ming; Chan, Kok-Gan; Goh, Bey-Hing; Mutalib, Nurul-Syakima Ab
Abstract : Background: Human gut microbiota – are normal flora living freely in the human gastrointestinal systems and this symbiotic bond begins at birth, and there are associations between human microbiota and skin allergens. Methods: This systematic review provides an insight into the role and condition of human microbiota that affects skin dermatitis and eczema. A thorough search was conducted using predefined terms in several electronic databases (PubMed, Medline, ScienceDirect), from database inception to March 2018. Studies must involve human microbiota, dermatitis, eczema, and full texts needed to be available. A total of 20 eligible articles were identified. Results: Based on the literature, several factors involving gut microbiota were identified that could affect skin dermatitis and eczema. Findings suggest that the dysbiosis of allergy in adults develops postnatally. At infancy stage, colonisation of the gut microbiota takes place and affects the immune development into the adolescence and adulthood. Hence, maternal milk represents a key factor to build ad modulate establishment of infant gut microbiota. Low level of IgA and IgE secretion in the gut system could reduce gut microbiota diversity. These antibody levels could be used to determine the establishment of a healthy symbiosis with gut microbiota. Interactions between dysbiosis in Faecalibacterium prausnitzii and gut epithelial is noted as underlie cause for the progression of dermatitis. In addition, studies reported a reduction of the abundance of Bifidobacterium in the gut microbiota had been seen in infants with eczema. A variation of Bifidobacterium colonisation patterns in early life is said to be associated with later development of eczema or dermatitis. Figure 1 illustrates what happens when an alteration takes action to the normal microbiome flora such as Bifidobacterial, Escherichia coli and Lactobacilli . This leads to the development of dermatitis and eczema. Conclusions: In summary, probiotics can enhance and maintain a healthy gut microbiota. Studies also suggested prenatal and postnatal supplementation of bifidobacterial may be effective in the primary prevention of allergy diseases. These findings provide vital insight and knowledge that could enhance the potential for future microbial-based therapies to improve the clinical outcome of dermatitis and eczema.